Bacillus subtilis relG Mutant: Defect in Glucose Uptake - Price, Virginia L. (1983)
A previously described Bacillus subtilis mutant which exhibits a relaxed phenotype after glucose limitation (relG) has been characterized further. Analysis of this mutant and of the downshift mechanism in B. subtilis has shown that the primary defect lies in glucose uptake.